Creditor Rights, Country Governance, and Corporate Cash Holdings - Bruce Seifert; Olubunmi Faleye; Halit Gonenc (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This study examines the impact of creditor rights on cash holdings using a sample of firms from 48 countries. We argue that creditor rights affect the willingness of lenders to provide credit, which in turn affects the need for internal liquidity and cash holdings. Consistent with this, we find that corporate cash holdings decline with the strength of creditor rights. We also find that this relation depends on the quality of country governance. Among well-governed countries, firms hold less cash as creditor rights strengthen. In contrast, cash holdings increase with creditor rights in poorly governed countries. In these countries, it appears that the fear of expropriation motivates creditors with stronger rights to require higher levels of cash holding by borrowers.
Keywords: G34; G32; G15; 330; Corporate governance; Cash levels; Creditor rights; International markets; Corporate Governance; Betriebliche Liquidität; Kreditsicherung; Sachenrecht; Welt